On a Question of Erdős and Gimbel on the Cochromatic Number - Heckel, Annika (The Electronic Journal of Combinatorics, 2024)
In this note, we show that the difference between the chromatic and the cochromatic number of the random graph $G_{n,1/2}$ is not whp bounded by $n^{1/2-o(1)}$, addressing a question of Erdős and Gimbel.